Bat optimization algorithm with fuzzy based PIT sharing (BF-PIT) algorithm for Named Data Networking (NDN) - Uma Maheswari P.; Manickam P.; Sathesh Kumar K.; Maseleno A.; Shankar K. (IOS Press, 2023)
Computer circuits; Nearest neighbor search; Network architecture; Networks (circuits); Content delivery; Data packet; Internet modeling; K Nearest Neighbor (k NN) algorithm; Management scheme; Named data networkings; Node selection; Optimization algorithms; Fuzzy logic